1977
DOI: 10.1185/03007997709115279
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pentoxifylline on Erythrocyte Deformability and on Phosphatide Fatty Acid Distribution in the Erythrocyte Membrane

Abstract: Ten maturity-onset diabetics with chronic vascular disease were treated with 400 mg pentoxifylline 3-times daily for 14 days. Erythrocyte deformability (using a filtration technique for whole blood) and phosphatide fatty acid distribution in the erythrocyte membrane were measured before and after the treatment period. Statistical analysis of the data showed that the erythrocyte filtration rate had increased significantly by the end of treatment (2alpha = 0.02), and that there were only slight changes in erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…12 The exact mechanisms of action of PTX in improving microcirculatory flow and tissue oxygenation remain to be determined but may be 1) increase of erythrocyte deformability 13 - 16 by raising ATP content, 17 2) inhibition of platelet aggregation, 18 " 20 and 3) reduction of plasma fibrinogen concentrations. 21 These effects of PTX may contribute to the reduction of whole blood viscosity.…”
mentioning
confidence: 99%
“…12 The exact mechanisms of action of PTX in improving microcirculatory flow and tissue oxygenation remain to be determined but may be 1) increase of erythrocyte deformability 13 - 16 by raising ATP content, 17 2) inhibition of platelet aggregation, 18 " 20 and 3) reduction of plasma fibrinogen concentrations. 21 These effects of PTX may contribute to the reduction of whole blood viscosity.…”
mentioning
confidence: 99%
“…A recent study demonstrated that the elastic modulus of RBC was decreased by Pentoxifylline treatment in vivo , which improved blood flow in subjects with cerebrovascular and peripheral arterial diseases ( Aifantis et al, 2019 ). Pentoxifylline is postulated to increase intracellular ATP concentrations, decrease Ca 2+ concentrations by activation of the Ca 2+ —Mg 2+ ATPase and calmodulin, and increase the phosphorylation of proteins into the RBC membrane ( Schubotz and Mühlfellner, 1977 ; Aifantis et al, 2019 ), which could increase RBC deformability. We previously demonstrated that tyrosine phosphorylation of membrane proteins was increased by the application of Pentoxifylline in vitro and was accompanied by an increase of RBC deformability in healthy donors ( Ugurel et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one might hypothesize that pentoxifylline affects red‐cell deformability. In rats receiving cyclosporine A, an immunosuppressant causing an increase in blood viscosity by a decrease in erythrocyte deformability, pentoxifylline was able to completely reverse these effects and thereby increase the glomerular filtration rate and renal plasma flow (19). A pentoxifylline‐induced increase in fatty acid composition of the red‐cell membrane has been hypothesized to be responsible for the improvement of red‐cell deformability.…”
Section: Discussionmentioning
confidence: 99%